Ecological Politics: The Role of the Term 'Environmentally Friendly' in Legitimizing Industrial and Government Activities - Rifqi Rifqi; Abdillah Syaikhon (Lentera Demokrasi: Jurnal Ilmu Sosial, Politik, Hukum, Ekonomi dan Pemerintahan, 2025)
The discourse of being environmentally friendly has become increasingly prevalent in various aspects of life, often associated with terms like go green, ecotechnology, and biodiversity. This concept, originally aimed at encouraging environmental conservation and mitigating global warming, is sometimes utilized superficially to legitimize industrial and governmental activities. Products and actions labeled as environmentally friendly, from household items to large-scale projects, frequently use this designation more as a marketing or legitimizing tool than a genuine commitment to sustainable practices. Through the lens of ecological politics, it becomes evident that this discourse can mask underlying social and environmental injustices. Ecological politics, influenced by neo-Marxian thought, critiques the superficial use of the environmentally friendly label, highlighting how power dynamics and economic inequalities contribute to environmental degradation. This approach urges a critical examination of such labels, revealing their potential to serve as symbolic violence and perpetuate social inequality. The need for raising public awareness about the true impact of these discourses is emphasized, promoting a critical perspective on the empirical reality of environmentally friendly claims. This abstract underscores the importance of scrutinizing the authenticity of environmentally friendly initiatives, advocating for a more profound and genuine commitment to environmental justice and sustainability.